Improvement in Neisseria gonorrhoeae culture using modified fastidious broth - Simmawong, Wiriya; Teeraputon, Sirilak; Wongsena, Wachanan (Journal of Associated Medical Sciences, 2024)
Background: Culture of Neisseria gonorrhoeae is essential for antimicrobial susceptibility testing and drug resistance surveillance. However, the success rate for N. gonorrhoeae culture from samples collected at sexually transmitted disease clinics is low. Moreover, culturing this fastidious organism can be challenging. Objective: This study aimed to develop and evaluate a modified fastidious broth (mFB) for improved preservation and culture of N. gonorrhoeae that would serve as both a transport medium for specimen collection from patients with suspected gonococcal infections and a growth enhancer for N. gonorrhoeae culture. Materials and methods: The mFB was evaluated using five standard bacteria strains at a concentration of 105 , 103 , and 101 CFU/ml: N. gonorrhoeae, Streptococcus agalactiae, Listeria monocytogenes, Escherichia coli, and Staphylococcus saprophyticus. After that, the mFB was used to collect specimens from 29 patients (77 samples) at the Venereal Disease Clinic at Mae Sot Hospital in Tak Province, Thailand, between October 2023 and February 2024. A total of 77 specimens were divided into 2 groups according to the gram-negative diplococci in Gram stain: 1) positive results (8 specimens) and 2) negative results (69 specimens). Furthermore, the N. gonorrhoeae culture was compared by using mFB on Chocolate agar (CA) and the direct plate specimen culture on Thayer Martin agar (TMA). Results: The results showed that the mFB could inhibit the growth of E. coli, L. monocytogenes, S. agalactiae, and S. saprophyticus but did not affect the growth of N. gonorrhoeae and significantly enhanced its growth. Using mFB, N. gonorrhoeae recovered 100% (8/8) of the positive Gram stain results from 77 clinical specimens, while direct TMA culture only recovered 75% (6/8). In addition, mFB enabled the detection of N. gonorrhoeae in 2 of the 69 Gram stain-negative specimens that were negative by direct TMA culture. Conclusion: N. gonorrhoeae culture using mFB, followed by subculture on CA, indicated that the mFB can preserve N. gonorrhoeae in clinical specimens during delivery to the laboratory and promote its growth. This has the potential to improve gonorrhea diagnosis and treatment with appropriate antibiotics, as well as enhance surveillance of antimicrobial-resistant gonorrhea.